2019
DOI: 10.3390/biomedicines7010015
|View full text |Cite
|
Sign up to set email alerts
|

On Zebrafish Disease Models and Matters of the Heart

Abstract: Coronary artery disease (CAD) is the leading form of cardiovascular disease (CVD), which is the primary cause of mortality worldwide. It is a complex disease with genetic and environmental risk factor contributions. Reports in human and mammalian models elucidate age-associated changes in cardiac function. The diverse mechanisms involved in cardiac diseases remain at the center of the research interest to identify novel strategies for prevention and therapy. Zebrafish (Danio rerio) have emerged as a valuable v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 118 publications
(132 reference statements)
0
31
0
Order By: Relevance
“…Additionally, biological characteristics, ease of genetic manipulation, facilitation of chemical screening, and genetic similarity to humans are features that contributed to zebrafish as a versatile animal model for cardiovascular research. Previously, zebrafish have been generated to study lipid metabolism and hypercholesteremia, major risk factors for cardiovascular disease [3]. Furthermore, Chen et al reported mutations in zebrafish, useful for in-depth cardiac development research [7].…”
Section: Why Zebrafish Behavior Is a Good In Vivo Model To Address Camentioning
confidence: 99%
“…Additionally, biological characteristics, ease of genetic manipulation, facilitation of chemical screening, and genetic similarity to humans are features that contributed to zebrafish as a versatile animal model for cardiovascular research. Previously, zebrafish have been generated to study lipid metabolism and hypercholesteremia, major risk factors for cardiovascular disease [3]. Furthermore, Chen et al reported mutations in zebrafish, useful for in-depth cardiac development research [7].…”
Section: Why Zebrafish Behavior Is a Good In Vivo Model To Address Camentioning
confidence: 99%
“…Nevertheless, despite its simplicity, genes, molecular signaling cascades and cellular processes that orchestrate the development of the heart are grossly conserved between zebrafish and mammals including humans. Additionally, cardiac physiology including heart rate, cardiac contractility, mechano-transduction as well as electrophysiological properties is highly similar between zebrafish and humans [18,[22][23][24]. For example, 3 days post-fertilization, the zebrafish heartbeats 150 times per minute which is much closer to the human situation than the mouse heart that beats appr.…”
Section: Aspects and Pitfalls During The Early Phase Of Cardiovasculamentioning
confidence: 99%
“…It is important to note that following cardiac damage, such as MI (humans) or cryoinjury (zebrafish), the initial phases from injury to repair and scarring are conserved, further strengthening the value of the zebrafish as a powerful tool to understand the limiting factors preventing mammalian regeneration ( Fig. 1 and reviewed by Giardoglou and Beis 2019). Both human and zebrafish repair involves an initial inflammatory phase (defined by the recruitment of immune cells and the clearance of cellular debris by phagocytosis) followed by a reparative phase characterised by deposition of collagen and other extracellular matrix (ECM) components and scar formation (Dobaczewski et al 2011;Chablais and Jazwinska 2012).…”
Section: Zebrafish As a Model For Repair And Regenerationmentioning
confidence: 99%